PERANAN BANK PERKREDITAN RAKYAT ( BPR ) DALAM MENINGKATKAN KEGIATAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI NUSA TENGGARA BARAT - ARTIKA, IDA BAGUS EKA; MARINI, IDA AYU KETUT (GANEC SWARA, 2023)
Micro, small and medium enterprise (MSME) activities are the real sector that produces products (goods and services), which will directly drive the economic wheels of society in a region. This sector requires support from the active role of the financial services industry, namely banking services. A study on the role of BPRs in improving MSME activities was carried out in the Bank Indonesia Mataram working area, in West Nusa Tenggara Province, in the form of a literature review of related published data. From the results of the study, the value of credit for MSMEs distributed by the banking industry in the West Nusa Tenggara Province region, until the end of 2022, amounts to IDR. 19.474431 trillion consisting of working capital credit amounting to Rp. 16.548945 trillion and investment credit Rp. 2.925486 trillion . Of all the MSME loans disbursed, Rural Banks on average only distributed 7.36 percent of the MSME loans disbursed. This credit was distributed by 28 BPR units in the West Nusa Tenggara region, consisting of 115 service offices spread throughout the West Nusa Tenggara region. Seeing that BPR's role in channeling MSME credit is still relatively small, this means that BPR must continue to strengthen its position, to increase its role as a microfinance institution that can support micro, small and medium enterprises in the West Nusa Tenggara Province region.